It has always been a man’s world: The woman as other in the Shona and Ndebele proverb - Mapara, Jacob; Thebe, Simangenkosi (Advances in Social Sciences Research Journal, 2015)
The paper argues that despite assertions that have been made in some circles that women have been treated as equal to men in pre-colonial Zimbabwe, an analysis of both Shona and Ndebele proverbs yields evidence that is to the contrary. It goes on to argue that both Shona and Ndebele societies have been patriarchal and have remained so up to this day. The researchers posit that these proverbs that have continued to be taught in Zimbabwean schools have been more of a celebration of the marginalisation of women than a celebration of culture. It argues that this is so because the proverbs have entrenched in the psyche of the young learners the erroneous notion of male superiority where the woman is perceived as the other while the man is the human being. The paper further argues that the way females are presented in both Shona and Ndebele proverbs is counterproductive since it conflicts with issues of gender and equality where women are accepted as equals, and yet the proverbs present them not only as lesser human but also in some instances as sex objects.